The effect of resistance training on some starting and achievement variables for discus throwers - Dawood , Abdul khaliq; Shamma , Haider (Journal of Physical Education, 2025)
The study aimed to design resistance training for discus throwers, identify their starting and performance variables, and examine the effect of resistance training on developing these variables. The researchers employed an experimental approach with two equivalent groups using pre- and post-tests, suitable for the research problem. The research population included female athletes participating in the Iraqi Athletics Clubs and Institutions Championship in November 2022, with 13 participants. Eight athletes were selected based on achievement levels and research requirements. They were randomly divided into two groups: an experimental group (4 athletes) training with resistance according to a graduated bumper network, and a control group (4 athletes) following standard trainer-led exercises. This represented 61.54% of the research population. The results showed that resistance training significantly improved starting angles, launch height, and discus velocity, with the bumper network playing a crucial role in angle adjustment and providing immediate feedback for technical corrections. The combination of resistance exercises and network-guided practice enhanced coordination, muscle activation, and overall performance. The study concluded that incorporating resistance training with a structured bumper network is highly effective in improving discus throwers’ technical and performance outcomes. Researchers recommended adopting such training methods to maximize achievement, develop biomechanical efficiency, and optimize launch angles for better results in competitive performance.